POTRET KERUKUNAN ANTAR UMAT BERAGAMA DALAM BINGKAI MODERASI BERAGAMA: STUDI KASUS DI DESA SIDODADI, MALANG - Sutrisno, Edy Sutrisno; Marsidi; Martino (Harmoni, 2024)
AbstractIndonesia, which consists of various tribes, races, religions, cultures, and languages, is a priceless wealth that needs to be processed well. So tolerance and moderation are needed to calm all groups, especially in matters of harmony between religious communities. The purpose of this writing is to determine the portrait of harmony between religious communities within the framework of religious moderation. Meanwhile, the research method uses a qualitative approach. The results of this research are: first, that the people of Sidodadi village, Gedangan subdistrict, and Malang district always appreciate and respect the existence and implementation of worship between religious communities, both Islam, Christianity, and Hinduism, and that there is no conflict between religious communities. Second, helping each other in building places of worship; this can be seen when Muslims, Christian congregations, and Hindus help each other in building places of worship voluntarily, and there is no coercion in helping to build these places of worship. Third, giving freedom in choosing the beliefs they adhere to. As in one family, there are several beliefs: Islam, Christianity, and Hinduism. Parents give their children complete freedom in choosing their religion, but their lives are always harmonious and peaceful. Then, when serving food at religious events, if those present are Muslims, then those who prepare the food are the Muslims themselves. AbstrakIndonesia yang terdiri dari berbagai suku, ras, agama, budaya dan bahasa merupakan kekayaan yang tak ternilai harganya sehingga perlu diolah dengan baik. Maka toleransi dan moderasi diperlukan untuk menenangkan semua kelompok, terutama dalam urusan kerukunan antar umat beragama. Tujuan dari penulisan ini adalah untuk mengetahui potret kerukunan antar umat beragama dalam bingkai moderasi beragama. Sedangkan metode penelitian menggunakan pendekatan kualitatif. Hasil penelitian ini adalah; Pertama, bahwa masyarakat desa Sidodadi kecamatan Gedangan kabupaten Malang selalu menghargai dan menghormati keberadaan dan pelaksanaan ibadah antar umat beragama, baik Islam, Kristen dan Hindu, dan tidak ada konflik antar umat beragama. Kedua, saling membantu dalam membangun tempat ibadah, hal ini terlihat ketika mendirikan tempat ibadah bagi umat Islam, jamaah Nasrani dan umat Hindu saling membantu dalam membangun tempat ibadah secara sukarela dan tidak ada paksaan dalam membantu pembangunan tempat ibadah tersebut. Ketiga, memberikan kebebasan dalam memilih keyakinan yang dianutnya, sebagaimana dalam satu keluarga terdapat beberapa keyakinan, ada Islam, Kristen dan Hindu, orang tua memberikan kebebasan penuh untuk anaknya dalam memilih agama, namun kehidupannya selalu rukun dan damai. Kemudian dalam hidangan makanan pada acara keagamaan jika yang hadir adalah umat Islam, maka yang menyiapkan makanan tersebut adalah umat Islam sendiri.